2005
DOI: 10.1016/j.ejheart.2004.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Relation between free triiodothyronine/free thyroxine ratio, echocardiographic parameters and mortality in dilated cardiomyopathy

Abstract: Background: Abnormalities in thyroid function are frequent in patients with heart failure and are associated with increased mortality. However, the relation between thyroid hormone levels and echocardiographic parameters has not been investigated sufficiently. Aim: The aims of this study were to investigate the correlations of thyroid hormone levels with echocardiographic parameters and to evaluate their associations with subsequent mortality in a group of patients with dilated cardiomyopathy (DCMP). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 23 publications
5
69
1
3
Order By: Relevance
“…Other changes in contractile proteins and regulators of sarcoplasmic calcium handling were found to be similar in heart failure and hypothyroidism [9][10][11]. In addition the echocardiographic ejection fraction and mortality was found to be significantly correlated with the serum thyrotropin concentration in dilated cardiomyopathy [23] and a low T3 syndrome, characterized by low circulating levels of the biologically active form of T3 in the presence of normal thyrotropin (TSH) and of thyroxine was reported to occur in approximately 30% of patients with advanced heart failure [12]. Serum-free T3 plasma levels in our DCM patients were significantly lower than in controls, but no subject had fT3 values lower than reference limits [12].…”
Section: Discussionmentioning
confidence: 78%
“…Other changes in contractile proteins and regulators of sarcoplasmic calcium handling were found to be similar in heart failure and hypothyroidism [9][10][11]. In addition the echocardiographic ejection fraction and mortality was found to be significantly correlated with the serum thyrotropin concentration in dilated cardiomyopathy [23] and a low T3 syndrome, characterized by low circulating levels of the biologically active form of T3 in the presence of normal thyrotropin (TSH) and of thyroxine was reported to occur in approximately 30% of patients with advanced heart failure [12]. Serum-free T3 plasma levels in our DCM patients were significantly lower than in controls, but no subject had fT3 values lower than reference limits [12].…”
Section: Discussionmentioning
confidence: 78%
“…11) Hypothyroidism and "low T3 syndrome," which represent decreased level of fT3 in common, are both the frequent comorbidities resulting to poor prognosis for patients with HF. 5,12) Our study demonstrated that even the low-normal level of fT3 (less than lower quartile) could influence the prognosis of HF patients after CRT implantation. It was an interesting result that fT3 might be a sensitive biomarker to detect the prognosis of HF patients receiving CRT.…”
Section: Discussionmentioning
confidence: 96%
“…Several factors have been implicated in low-T 3 syndrome, including: increased T 3 receptor expression, which may be responsible for maintaining euthyroidism in the face of reduced circulating thyroid hormone levels (Williams et al 1989); reduced enzyme activity of 5 0 -monodeiodinase, responsible for converting T 4 to T 3 in peripheral tissues (Mebis & Van den Berghe 2011); reduced plasma selenium concentration, a shared cofactor with antioxidant enzymes and deiodinases (Van Lente & Daher 1992); increased cytokine levels (Hermus et al 1992, Boelen et al 1995; and increased levels of Triac (T 3 analog) and/or Tetrac (T 4 analog), which may feedback to the pituitary/hypothalamus region and cause a secondary hypothyroidism (Carlin & Carlin 1993). Low-T 3 syndrome is also a strong prognostic predictor of death in patients with heart disease, giving additional information to the conventional clinical and functional cardiac parameters (Iervasi et al 2003, Kozdag et al 2005, Pingitore et al 2005.…”
Section: New Ras Componentsmentioning
confidence: 99%
“…The RAS in low-T 3 syndrome and subclinical thyroid disorders Changes in thyroid function parameters are observed in starvation and fasting, cardiac disease (Kozdag et al 2005, Pingitore et al 2005, renal disease (Lim et al 1980, Zoccali et al 2005, renal transplantation (Hekmat et al 2010), ageing (Tognini et al 2010), and increased saline intake (Cruz et al 2011), leading to low-T 3 syndrome (also known as non-thyroidal illness syndrome or euthyroid sick syndrome). This syndrome is characterized by low circulating T 3 levels and normal or decreased T 4 levels and, usually, by normal thyroid stimulating hormone (TSH) levels.…”
Section: New Ras Componentsmentioning
confidence: 99%